Sub-Saharan African Migration : Patterns and Spillovers - Gonzalez-Garcia, Jesus; Hitaj, Ermal; Mlachila, Montfort; Viseth, Arina (Washington, D.C. : International Monetary Fund, 2016)
Amid rapid population growth, migration in sub-Saharan Africa has been increasing briskly over the last 20 years. Up to the 1990s, the stock of migrants-citizens of one country living in another country-was dominated by intraregional migration, but over the last 15 years, migration outside the region has picked up sharply. In the coming decades, sub-Saharan African migration will be shaped by an ongoing demographic transition involving an enlargement of the working-age population, and migration outside the region, in particular to advanced economies, is set to continue expanding. This note explores the main drivers of sub-Saharan African migration, focusing on migration outside the region, as this has greater global spillovers. It finds that the economic impact of migration for the region occurs mainly through two channels. First, the migration of young and educated workers-brain drain-takes a toll as human capital is already scarce in the region, although some recent studies suggest that migration may have also a positive effect-brain gain. Second, remittances represent an important source of foreign exchange and income in a number of sub-Saharan African countries, contribute to the alleviation of poverty, and help smooth business cycles.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet